Properties of original and irradiated phosphide-gallium LEDs - M. Ye. Chumak; P. G. Lytovchenko; I. V. Petrenko; D. P. Stratilat; V. P. Tartachnyk (Âderna Fìzika ta Energetika, 2024)
Spectral features of the original and irradiated with electrons with E = 2 MeV GaP light emitting diodes (LEDs) were studied. Recombination lines of the exciton bound on the N isoelectronic center and on the pair complexes NN1 were detected. The change in the spectral composition of radiation when passing through a section of negative differential resistance is analyzed. Dose dependences of luminescence intensity were obtained for green GaP(N) and red GaP(Zn-O) LEDs. The maximum critical radiation dose was established, after which the LEDs lost their characteristic exciton emission mechanism. The results of the annealing of irradiated LEDs are given.